Species richness and conspecific associations of trees in Gunung Meja Nature Tourism Park, West Papua, Indonesia - WOLFRAM YAHYA MOFU; JONNI MARWA; AGUSTINUS MURDJOKO; CHARLIE DANNY HEATUBUN (Society for Indonesian Biodiversity, 2026)
Abstract. Mofu WY, Marwa J, Murdjoko A, Heatubun CD. 2026. Species richness and conspecific associations of trees in Gunung Meja Nature Tourism Park, West Papua, Indonesia. Biodiversitas 27 (7): d270720. https://doi.org/10.13057/biodiv/d270720. Tropical rainforests are critical for global ecosystem functioning, yet the ecological processes governing recruitment and structural growth in Papuan conservation forests remain poorly understood. We investigated species richness and conspecific associations within Gunung Meja Nature Tourism Park (GMNTP), a lowland tropical rainforest in West Papua, Indonesia, by collecting tree data from 50 plots and categorizing them into small (DBH < 10 cm) and large (DBH ≥ 10 cm) individuals. We documented 198 tree species, including 167 small-tree species and 130 large-tree species. Using the Importance Value Index (IVI), we found that small individuals had significantly higher IVIs. Conspecific association analysis revealed that 35.35% of species exist exclusively as small individuals, while 16.16% exist exclusively as large individuals. Hierarchical clustering demonstrated high dissimilarity in the understory (distance 30.0-60.0), contrasting with pronounced homogeneity in the canopy (distance < 18.0). These results provide evidence of intense ecological processes, driven by resource competition and conspecific negative feedback, which narrow the high-diversity recruitment pool into a convergent mature community. Our findings indicate that GMNTP can serve as a